Discovery and discussion methods in teaching ulumul qur’an at an Islamic higher education institution - Syafrudin, Syafrudin; Fuadah, Tsani Tsamrotul; Nurhasanah, Nurhasanah (Al-Liqo: Jurnal Pendidikan Islam, 2025)
This study examines pedagogical challenges in teaching Ulūmul Qur’ān in the Islamic Education Management Program at STAI Idrisiyyah, particularly low engagement and shallow understanding resulting from lecture-based instruction. It investigates the implementation of a collaborative discovery learning–discussion model and its impact on cognitive outcomes and intrinsic motivation. Using a qualitative case study approach, data were collected through interviews, observation of 12 learning sessions, and document analysis. The findings indicate a 45% improvement in students’ analytical skills on topics such as nasikh-mansukh and makki-madani, alongside a 40% increase in classroom participation. The model encourages epistemic agency through guided inquiry, discussion, and double-loop learning, integrating tadabbur and mudzākara. This hybrid approach contributes to Islamic pedagogy by strengthening analytical competence and collaborative learning in Qur’anic higher education.